Peningkatan Pemahaman Konsep Dalam Pembelajaran Matematika Melalui Pendekatan Reciprocal Teaching (PTK di SMP Muhammadiyah 10 Surakarta Kelas IX Semester Gasal Tahun Ajaran 2015/2016) - Vristiarum, Rida (2016)
The purpose of this study was to improve understanding of concepts in mathematics students in grade IX C SMP Muhammadiyah 10 Surakarta approach Reciprocal Teaching. The benefits of this research is discovering new knowledge about improved understanding in learning mathematics through approach Reciprocal Teaching. This study used a qualitative research based on the function with the design of classroom action research. This research was conducted with the collaboration between researchers math teacher. Students of class IX C with a number of 21 students act as recipient action subjects. Teachers of mathematics as a subject of the perpetrator. Principals and teaching staff as an auxiliary subject. In this study the method of data collection is done by the method of observation, tests, field notes, and documentation. The validity of the data using triangulation investigator. Data analysis techniques including data collection, data reduction, data display, and conclusion. From the results of the study showed an increased understanding of the concept of students' learning of mathematics. The improvement can be seen from a) The ability of students to apply concepts precisely from (23.81%) increased to (66.67%), b) the ability of the students to answer questions from the teacher (28.57%) increased to (76.20% ), c) Ability to work on the problems in front of the class (33.33%) increased to (66.67%), d) ability of the students concluded the material presented includes the definition of the concept as well as provide examples and non-examples of the concept of (14.29 %) increased to (71.43%). Learning mathematics using Reciprocal Teaching approach can enhance students' understanding of the concept.